A new approach to measure sustainability in German facility management. Issue 1 (1st February 2016) - Graubner, Carl-Alexander; Pelzeter, Andrea; Pohl, Sebastian
Abstract : Purpose: – The purpose of this paper is to present the development of an action and assessment framework to make sustainability in German facility management (FM) transparent, measurable and assessable. Design/methodology/approach: – The underlying research project's approach to develop the new action and assessment framework consisted of a three-step methodology: to define and substantiate sustainability in FM, to operationalise and quantify sustainability in FM and to validate the developed system draft through an initial pilot study. Findings: – The main result of the presented research project is a set of 24 criteria, organised into the separate areas of environmental, economic and sociocultural quality, as well as the quality of FM organisation and the sustainability of building/contract-specific facility services. The assessment methodology reflects the strategic approach of a plan–do–check–act loop to create a transparent and objective appraisal and a practical action framework. Research limitations/implications: – The outcome of the study is initially only a measurement and assessment framework. To transform the finalised system draft and assessment tool into a certification system, further steps of development are necessary. Practical implications: – The newly developed action and assessment framework is able to cure the blind spot that the relevant players (building owners, users and service providers) suffer from while developing, purchasing and comparing concepts for sustainable FM. The results and practical experiences of its initial pilot study show that this new framework can make the building operation phase and its processes transparent, measurable and assessable. Social implications: – The guideline is also able to establish a crucial basis for the development of corporate sustainability strategies and sustainability reporting. This is an important step in closing the existing gap in numerous corporate social responsibility reports. Originality/value: – Due to its assessment methodology and the calibration of its criteria, this new action and assessment framework both diversifies and completes the range of existing sustainability certification systems.